IMPLEMENTASI KURIKULUM BERBASIS KOMPETENSI (KBK) DI PERGURUAN TINGGI AGAMA ISLAM (Studi Kasus di Fakultas Tarbiyah UIN Malang) - Sulalah Sulalah (El-QUDWAH, 2006)
Implementation of Competence Based Curriculum (KBK) in Islamic Higher Education Intitution (PTAI) especially in Islamic Education Faculty UIN Malang nedds 10 step, such as: (1) Deciding vision and mission PTAI including function and duty among PTAI graduate, (2) Deciding competent standard of graduate, points of  competence and indicator based on vision mission of PTAI graduate; (3) Deciding competent standard of curriculum materials; (4) Deciding competent standard of each subject; (5) Deciding syllabus, (6) Selection of teaching material, (7) implementation of competent based curriculum in teaching process, (8) Teaching process based on KBK results in competent graduate, (9) Supervision and advisory from the authority such as Education Department, Religious Affair Departement, Rector, Dean, The Head of Program, and other institution to produce competent graduate and to follow up quality implovement of KBK implementation in PTAI, (10) To gain feed back  from KBK implementation as a base to improve and implement curriculum that is in line with need and challenging era.Key words: Implementation, KBK, PTAI